Medication Regimen Complexity and Medication Adherence In Patients with Polypharmacy: Pharmaceutical Sciences-Pharmacy for better health - GnanaSwarupin, Ms.K.; Prabha, G.RamyaBala; Santhosha, Dharmapuram; Hepciba, Nadimidoddi (International Journal of Life Science and Pharma Research, 2021)
The complexity of medication regimen can be defined by the number of medications (polypharmacy) and the number of times per day or dose. The term medication adherence is defined by WHO as the extent to which a perosn’s behavior agrees with the agreed medication regimen from a healthcare provider. . The main objective of the study is to implement medication regimen complexity index in patients with polypharmacy and to evaluate the rate of medication adherence in polypharmacy patients and also the factors affecting for non adherence Hospital based prospective case study was conducted for a period of 8 months after obtaining permission from Institutional Ethical Committee, CMR College of Pharmacy, Hyderabad. Data was collected and analysed according to inclusion and exclusion criteria. A total of 165 cases were included and analyzed for the study and was found that the most common age group with polypharmacy was between 51-60 years with male predominance. Study observation reveals that most of the uneducated patients are non adherent to their medication. The low complexity MRCI score included tracks between 6.0 to 13.0, while the high complexity MRCI score included tracks of 13.0 to 22.5. Most of the elderly patients were found to have high complexity. Among 165 patients, 98 were non-adherent and 67 were adherent to treatment regimen. i.e, most of the patients were non adherent to medications. Present study concludes that elderly patients were present with higher regimen complexity than adults and older adults. Most of the polypharmacy patients were found to have high regimen complexity with score of 15. Most of the patients were found to be non adherent to the therapy in polypharmacy patients.